Návrh cvičného pokračovacího a lehkého bojového letounu - Kohout, John; Kohout John (České vysoké učení technické v Praze, 2017)
Cílem práce je provést přehled a srovnání výkonových parametrů letounu AJT v základní a modifikonvané konfiguraci s novým profilem křídla a současně pro stávající motor a motor AI-222-30. Na závěr posoudit změny v konstrukci draku letounu s ohledem na zástavbu motoru.

The aim of this thesis is to analyze and comply a feasbility study of performance on aircraft AJT and it's modified version with upgraded airfoil, aswell compare it with original power plant unit and new proposed unit AI-222-30. Lastly analyze the changes that would have to be made with the engine compartment.
Design of an advanced training and light combat aircraft
Keywords: Aerodynamika,mechanika letu,výkony,pohonná jednotka; aerodynamics,mechnics of flight,performance,power plant